Analisis peraturan perkawinan beda agama di berbagai negara sebagai perlindungan hukum untuk membentuk keluarga - Kadek Wiwik Indrayanti; Enny Ristanty (University of Merdeka Malang, 2020)
The validity of interfaith marriages for Indonesian citizens is not regulated in the provisions of Law No. 1 of 1974 as amended by Law No. 16 of 2019 concerning marriages, while the fact of citizens who engage in interfaith marriages is increasing. A comparative study of marriage regulations in several countries aims to gain holistic knowledge and understanding of the regulations governing marriages, specifically the similarities and differences in marriages of different religions. So that the future can be used as input in regulating the rules of interfaith marriages in Indonesia. The research method used to analyze this study is normative legal research because it uses a comparative approach to law in several countries. The results show that the validity of marriages in several countries such as the USA, Australia, Singapore and the Netherlands is done through registration. Almost all countries used as objects of study regulate interfaith marriages. So that the protection of the right to form a family is guaranteed. Turkey which has similarities with Indonesia regulates interfaith marriages.How to cite item: Indrayanti, K., Ristanty, E. (2020). Analisis peraturan perkawinan beda agama di berbagai negara sebagai perlindungan hukum untuk membentuk keluarga. Jurnal Cakrawala Hukum, 11(1), 71-81. doi:https://doi.org/10.26905/idjch.v11i1.4046